2016
DOI: 10.1111/jnc.13670
|View full text |Cite
|
Sign up to set email alerts
|

Diversity matters – heterogeneity of dopaminergic neurons in the ventral mesencephalon and its relation to Parkinson's Disease

Abstract: Dopaminergic neurons in the ventral mesencephalon (the ventral mesencephalic dopaminergic complex) are known for their role in a multitude of behaviors, including cognition, reward, addiction and voluntary movement. Dysfunctions of these neurons are the underlying cause of various neuropsychiatric disorders, such as depression, addiction and schizophrenia. In addition, Parkinson's disease (PD), which is the second most common degenerative disease in developed countries, is characterized by the degeneration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 174 publications
(309 reference statements)
2
57
0
Order By: Relevance
“…Taken together, these data suggest that Mest has a crucial role in the maintenance of SNc neurons. During the progression of PD, neurons in the ventral tier and medial tier of the SNc are lost before the disease affects the entire SNc (Braak et al, 2003, 2004; Vogt Weisenhorn et al, 2016). Interestingly, the progressive loss of mdDA neurons detected in the SNc of Mest neurons partly resembles this loss as seen in PD, indicating that the Mest ablated mouse model may serve to study degeneration events as observed in PD.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these data suggest that Mest has a crucial role in the maintenance of SNc neurons. During the progression of PD, neurons in the ventral tier and medial tier of the SNc are lost before the disease affects the entire SNc (Braak et al, 2003, 2004; Vogt Weisenhorn et al, 2016). Interestingly, the progressive loss of mdDA neurons detected in the SNc of Mest neurons partly resembles this loss as seen in PD, indicating that the Mest ablated mouse model may serve to study degeneration events as observed in PD.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of brain region will depend on the initial hypothesis. For example, TH+ cells may be quantified in the ventral tegmental area; part of the mesolimbic pathway where dopaminergic neurons project to the striatum, known to be abnormal in schizophrenia (Brisch et al., ; Vogt Weisenhorn, Giesert, & Wurst, ; for an example analysis of TH+ cells see Salminen et al., ). An additional endophenotype of schizophrenia is a reduction in PV+ interneurons or expression in the prefrontal cortex (Volk & Lewis, ).…”
Section: Commentarymentioning
confidence: 99%
“…Vogt Weisenhorn and colleagues describe the inhomogeneity of dopaminergic neurons (Vogt Weisenhorn et al . ). The diversity of mesencephalic dopaminergic neurons not only comprises diverse functions, afferent, and efferent connections but also diverse gene expression with a dynamic molecular variability.…”
mentioning
confidence: 97%
“…To date, the question of selective vulnerability of dopaminergic neurons of the substantia nigra remains unansweredin fact only a subset of dopaminergic neurons in the mesencephalon is selectively vulnerable. Vogt Weisenhorn and colleagues describe the inhomogeneity of dopaminergic neurons (Vogt Weisenhorn et al 2016). The diversity of mesencephalic dopaminergic neurons not only comprises diverse functions, afferent, and efferent connections but also diverse gene expression with a dynamic molecular variability.…”
mentioning
confidence: 99%